Alcohol use and depression from middle age to the oldest old: Gender is more important than age - Tait, Robert; French, D.; Burns, R.; Anstey, K. (Cambridge University Press, 2012)
Background: Alcohol use disorders are associated with other mental health disorders in young adults, but there are few data on alcohol use and mental health outcomes in older adults, particularly the oldest old. This study examines the relationship between alcohol consumption and depressive symptoms. Methods: Data were collected from the Dynamic Analyses to Optimise Ageing (DYNOPTA) project, which has pooled nine Australian longitudinal studies. Alcohol consumption was classified using standard drinks (10 g alcohol)/day as: abstinent, low risk (<0–≤2 standard drinks), long-term risk (>2–≤4) and short-term risk (>4). Probable depression was classified from harmonized scores on various standard instruments (e.g. Centre for Epidemiological Studies Depression scale). Results: Overall, 39,104 (86%) participants contributed data. Alcohol classification at baseline showed 7,526 abstinent, 28,112 low risk, 2,271 long-term risk, and 1,195 short-term risk participants. Age ranged from 45 to 103 year (median 60). Using generalized estimating equations (GEE), there were significant gender by alcohol and gender by age interactions, so the analysis was split by gender. Among males, the abstinent and short-term risk groups had increased likelihood of depression: in females the abstinent, long- and short-term risk groups had increased odds of depression. Increased odds of depression was also associated with former and current smoking, younger age-group, not being partnered, leaving school before age 15 and increasing levels of health-impaired walking, dressing, or bathing. Conclusion: The impact of alcohol use differs by gender, nevertheless those using higher levels of alcohol or who smoke should be screened for depression and may benefit from interventions.